Dinamika Ekonomi Rumah Tangga Nelayan Tradisional: Studi Kasus di Kabupaten Situbondo - Laily, Dona Wahyuning; Rizkiyah, Noor; Tondang, Ika Sari; Rozci, Fatchur; Fitriana, Nisa Hafi Idhoh (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The purpose of this study was to determine (1) Factors that affect the income of fishing households, and (2) factors that affect the expenditure of fishing households, and to analyze them, (3) The possibility of poverty caused by factors that affect poverty among fishing communities in Jangkar District, Situbondo Regency. The samples collected in this study were fishing communities using random sampling. The results of the study showed that (1) the characteristics of fishermen were 42.39% of fishermen aged between 41 and 50 years, while the majority of fishermen's education level was at elementary school (SD) level, which was 35.64%. Based on fishing experience, around 36.9% were aged between 21 and 30 years, and the number of fishing families was 51.80%, with the majority consisting of 3 people or less. While the employment status of fishermen was around 43.76%, (2) factors that affect fishing income are education, fishing experience, and fishing boat engines, (3) factors that affect fishing household expenditure are the number of family members. (4) Factors that influence the risk of poverty in fishermen are the age of fishermen, education, and experience. The aging of fishermen increases the risk of poverty, but training and experience at sea. The increasing age of fishermen will increase the chances of poverty, but increasing the education factor of fishermen and experience in working as fishermen will reduce the level of poverty in fishermen's households.